Halo 194? Ovde COVID-19 - Čolaković, Goran; Andjelic, Sladjana; Nacic, Mirela (Halo 194 Scientific Journal of Emergency Medicine, 2020)
The emergency call center (ECC) is the first link of the chain of survival and the heart of the entire pre-hospital segment of the health care system (HCS). Following the decision to declare a state of emergency (SE) in Serbia due to the COVID-19 pandemic, CC 194 in Belgrade ECC was fully in the service of the SE and recommended instructions of the Ministry of Health (MH) of the Republic of Serbia. In addition to regular activities in the ECC, through a direct telephone line the so-called COVID-19 lines, operators answered phone calls related to coronavirus infection.We presents the number of connections made on the COVID-19 line in Belgrade, a city with nearly 2 million inhabitants, during the SE in the period from February 15 to April 6, 2020.